1997
DOI: 10.1177/104973239700700304
|View full text |Cite
|
Sign up to set email alerts
|

Nerves as Status and Nerves as Stigma: Idioms of Distress and Social Action in Newfoundland and Northern Norway

Abstract: The nature of the cross-culturally occurring folk or popular complaint of nerves as a form of psychosomatic illness and idiom of distress has been speculated on by a wide variety of scholars. Much of the research seeks to identify common symptomatologies with universal, diagnostic equivalents and/or seeks to expand on the more distinctive metaphorical qualities of nerves as an idiom of distress. Comparison and contrast of anthropological studies of two fishing villages (one in Newfoundland and one in Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…If someone they knew passed by, they would take a break or stop. The following two cases also illustrate that the public and private natures of nerves are more complex than Davis and Joakimsen's (1997) study found.…”
Section: Nerves: Sharing In the Realm Of Privacymentioning
confidence: 87%
See 1 more Smart Citation
“…If someone they knew passed by, they would take a break or stop. The following two cases also illustrate that the public and private natures of nerves are more complex than Davis and Joakimsen's (1997) study found.…”
Section: Nerves: Sharing In the Realm Of Privacymentioning
confidence: 87%
“…I compared and contrasted this material from Solnes with that of Fagerstrand (Davis & Joakimsen, 1997) to identify and reassess complexities that underlie the concepts of stigma in Northern Norway.…”
Section: Methodsmentioning
confidence: 98%
“…Terms such as depression or nerves have a dramatic social impact because they are linked to cultural models interrelating ideas about causation, responsibility, outcome, and personal character. Stigma and social support, for example, emerge from the use of illness terms as a result of associated inferences derived from cultural models (Camino 1989; Davis and Joakimsen 1997; Dressler 1985; Finkler 1985; Monks 1995; Skultans 2003, 2007; Steffen 1997; Thurston 1987; Waxler 1981; Yang and Kleinman 2008). …”
Section: Toward a Third Approach: Cultural Models And Embodied Experimentioning
confidence: 99%
“…Anthropologists have studied nerves as a symbol and social tool, folk idiom or lay idiom of distress (Davis 1989(Davis , 1997Guarnaccia and Farias 1988;Migliore 1993;Nations et al 1988;Nichter 1981;Parsons and Wakeley 1984), an ineffective idiom of distress (Camino 1989), a folk ailment (Rebhun 1993), a folk illness (Mathews 1987), a culture-bound syndrome or culture-specific complaint (Barlett and Low 1980;Dresp 1985;Low 1981), a culturally constructed episode (Guarnaccia and Farias 1988), a culturally interpreted syndrome (Low 1985), a metaphor or embodied metaphor (Low 1994;Scheper-Hughes and Lock 1986), an embodiment of distress (Lyon and Barbalet 1994;Traverso-Yepez and de Medeiros 2005), and as social commentary (Lock 1989;Reynolds and Swartz 1993;Scheper-Hughes and Lock 1986;Sobo 1996). This anthropological research has elucidated messages about morality and social commentary inherent in cultural models of distress, and highlighted the role of social interaction in constructing both lay and biomedical models.…”
Section: Focus On Context-bound ''Social Meanings'': An Anthropologicmentioning
confidence: 99%
“…In journal article form they focus on a small piece of a highly particular experience and illuminate it exquisitely. For example, Davis and Joakimson (1997) examined the folk illness of``nerves'' in two different yet similar cultural contexts: ®shing villages in Norway and Newfoundland. Despite many parallels in culture, access to medical care, and social construction of illness, the researchers demonstrated that the social milieu and social consequences of having nerves differed greatly in these two communities based on differences in the longevity and livelihood of the ®shing industry and in the strength and cohesion of women's social networks.…”
Section: Degrees Of Complexity and Discovery In Qualitative Findingsmentioning
confidence: 99%